Burnout syndrome among dentists of Health Centers from Acapulco, Mexico. - Ciprián Chavelas, Tatiana (2023)
Introduction: Burnout syndrome is professional burnout resulting from chronic work stress with a three-dimensional complex characterized by emotional exhaustion, depersonalization and personal fulfillment derived from work due to direct contact with patients. Objective: To estimate the frequency of severe burnout syndrome among dentists of Health Centers from Acapulco, Mexico. Material and methods: Cross-sectional design in a convenience sample of 80 dentists with the application of a self-administered questionnaire of 44 items during March to May 2022. The instrument contained the Maslach-Burnout Inventory of 22 items with Likert-type categorical responses, which established a global score with the sum of the three dimensions. A binary logistic regression analysis was applied based on the cut-off point established with SPSS V.24.0 statistical software. Results: The 50% of the dentists presented severe burnout. A related factor was found, the type of employment contract, in the category of temporary and fee contract (p=0.04). Conclusion: Actions should be taken to improve labor stability conditions for dentists, through the recognition of their work, in order to improve the types of contracting in public health institutions.